Empathetic Leadership, Job Satisfaction and Intention to Leave among Millennials in a Start-up Industry: Needs’ Satisfaction as a Mediating Variable - Muhammad Cesare Wicaksana Negoro; Amin Wibowo (Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
Introduction/Main Objectives: The purpose of this research is to examine the relationship between empathetic leadership and employees' job satisfaction and the intention to leave with needs’ satisfaction as a mediating variable among millennials in a start-up business. The number of millennials will only continue to grow, and by 2025 it is expected that 75% of the global workforce will be millennials. In particular, empathetic leadership will be required to manage and control this generation if the organizations they choose to work for are to be successful, as this generation’s members have different characteristics compared to those of the older generations. Design/methodology/approach: Following a cross-sectional research design, this research collected data from 137 millennial employees of start-up companies in Indonesia. A structural equation modeling technique was used for the data’s analysis. Findings: The results reveal that empathetic leadership has a direct and positive relationship with employees' job satisfaction and has a direct and negative relationship with the intention to leave. Needs’ satisfaction partially mediates these relationships. Originality: This study makes a novel contribution to the existing literature by first providing empirical evidence that among the three dimensions of needs’ satisfaction only the relatedness dimension passed the measurement test in the structural equation modeling. Second, empathetic leadership is proven to increase job satisfaction and reduce the intention to leave among millennials, considering their unique characteristics. Research limitations/implications: The research was conducted during COVID-19 pandemic. Circumstances related to that pandemic might influence the result of this study. It is, therefore suggested to conduct the study again under normal circumstances. Policy and Practical implications: The findings of this study suggest managers should develop an empathetic leadership style in order to better manage the millennials. Leaders can be nurtured, but disciplined efforts have to be invested in their creation.